Assessment of Knowledge, Attitudes, and Perceptions of Safety and Prevention Procedures among Butchers in Derna and Neighboring Areas / Libya - Salwa Muftah Eljamay; Fareha Hamd Younis; Ebtasam Muftah Alashger; Ramadan Saleh Eltuomi (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study assessed the knowledge attitude and practice of butchers in Derna City and nearby areas of Libya, aimed to gain Knowledge on meat handling of slaughterhouse workers in Derna, & the factors related to the knowledge, attitude and practices of slaughterhouse butchers in the Derna, Material & Methods: this was a descriptive cross-sectional study design that involved the use of quantitative methods. The study was conducted from different through personal interviews with butchers in the city of Derna and its suburbs, (Karssa, Martouba) and collecting questionnaires from them was completed from June 2021 to October 2021, Result: It is noticeable the percent of knowledge answered for Butcher, which receives vaccination (60%), which using PPE 58%, which check regally (66.7%), which know the discarded methods of wastes, (52.7%), which know the diseases which transmitted by meat (59.3%), which receive education program the control and prevention (44%). Conclusion: The results indicate that the study found no relationship between the extent of awareness of butchers and their practices in some questions and in some other questions there is no relationship between the level of education and awareness. Therefore, it is recommended to increase and intensify awareness lectures on prevention and control.